Service Quality Analysis to Increase Customer Satisfaction on the M-BCA Application - Rolin, Kendrick Nathanael (Journal of Current Research In Multidisciplinary, 2024)
This research aims to analyze whether service quality can increase customer satisfaction. Before starting gap analysis, the first step is to look for a solid and relevant research model foundation. From the intention-to-use model modified by DeLeon (2019), three variables were taken and adjusted for indicators of gap analysis: perceived usefulness, perceived ease of use, and trust propensity. 10 indicators of service and feature quality were determined as a result of the survey attached below. After compiling the indicators, the questionnaire was prepared based on a list of indicators using Google Forms with a 5-point Likert scale for both aspects of importance and performance. A total of 30 respondents with valid responses filled out the form, and the results of the responses were downloaded in xlsx form for analysis. The first process concerns the average results of the assessment of the importance and performance of 10 indicators. The difference (gap) is then calculated and made into a scatterplot-matrix graph. Based on research results, it shows that the banking industry is relatively unaffected by regulations and customer views that require certainty. However, according to research, incremental innovation is still needed for mobile banking applications, not in terms of drastic changes in a short time but slowly introducing small features that customers are educated about. In the long term, these honed features will become a selling point for potential customers because they have the advantage of rich capital and human resources to execute quickly.